CRESST cryogenic dark matter search - Cozzini C.; Henry S.; Kraus H.; Majorovits B.; Ramachers Y.; Angloher G.; Frank T.; Hauff D.; Ninkovic J.; Petricca F.; Probst F.; Seidel W.; et al. (2005, 2005)
Title screen